Qualitative Research in Business : a Practical Overview. - Walle, Alf H. (Cambridge Scholars Publishing, 2015)
Qualitative methods are today taking their rightful place as valuable and powerful research tools both in business and elsewhere. Many professionals, however, continue to lack the skills needed to apply these methods in an effective and convincing manner. Qualitative Methods in Business Research: A Practical Guidebook offers an analysis and "how to" guide regarding qualitative research methods that provides practical and effective advice for those seeking knowledge regarding the application o ...